CdSe and CsPbBr3 quantum dot Co-doped monolithic glasses as tunable wavelength convertors - Kibrisli, Orhan; Erol, Erdinc; Ersundu, Ali Ercin; Ersundu, Miray Celikbilek (IOP Publishing Ltd, 2022)
CdSe and CsPbBr3 quantum dots (QDs) are well studied photoluminescent materials due to their extraordinary emission properties. However, their vulnerability against environmental conditions limits their integration into further applications. At this point, glass encapsulation offers promising durability features due to its robust and dense structure. In this study, CdSe and CsPbBr3 QDs are successfully synthesized in the same glass host through the melt-quenching technique followed by a single heat-treatment process. Excitation wavelength dependent photoluminescence properties are investigated and emission color tunability of monolithic glasses from yellow-green to red is demonstrated. Favorable quantum yield values are obtained as 21.78% and 16.63% under 345 and 365 nm excitation wavelengths, respectively. The prepared glasses demonstrate high potential to be used as tunable wavelength convertors for state-of-the-art photonic and opto-electronic applications.
Keywords: quantum dot; glass; wavelength convertor; tunable; CRYSTALLIZATION; HOST; Physics